2002
DOI: 10.1103/physrevlett.89.237203
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Inhomogeneities in Manganite Thin Films Investigated with Scanning Tunneling Spectroscopy

Abstract: Thin films of La 0.7 Sr 0.3 MnO 3 on MgO show a metal insulator transition and colossal magnetoresistance. The shape of this transition can be explained by intrinsic spatial inhomogeneities, which give rise to a domain structure of conducting and insulating domains at the sub micrometer scale. These domains then undergo a percolation transition.The tunneling conductance and tunneling gap measured by scanning tunneling spectroscopy were used to distinguish and visualize these domains.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
124
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 21 publications
(24 reference statements)
8
124
0
Order By: Relevance
“…The intrinsic chemical inhomogeneity in the form of "clustered states" [13][14][15] has been regarded as a common feature of magnetic semiconductors, colossal magnetoresistance manganites, 16 and high temperature superconducting cuprates. The special chemical inhomogeneity has been found in Mn-doped Ge ferromagnetic semiconductors, 17 which show Mn-rich and Mn-depleted phases, rather than in metallic Mn clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic chemical inhomogeneity in the form of "clustered states" [13][14][15] has been regarded as a common feature of magnetic semiconductors, colossal magnetoresistance manganites, 16 and high temperature superconducting cuprates. The special chemical inhomogeneity has been found in Mn-doped Ge ferromagnetic semiconductors, 17 which show Mn-rich and Mn-depleted phases, rather than in metallic Mn clusters.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, it has been extensively reported that Curie temperature and magnetic moment of the ferromagnetic (FM) manganite films decreases as the films become thinner, which has been ascribed to both extrinsic and intrinsic effects such as structural and compositional inhomogeneities, interfacial charge transfer, and straininduced orbital reconstruction. [7][8][9][10][11] In a flurry of recent studies, ultrathin manganite films were incorporated in epitaxial heterostructures as a result of expectation of emergent physics such as tailored interfacial magnetic coupling and geometrically confined doping in such artificial lowdimensional systems. [12][13][14][15] Epitaxial superlattices (SLs) of complex oxides give access to fascinating physical phenomena as a result of magnetic frustration, charge transfer, and orbital reconstruction across interfaces.…”
mentioning
confidence: 99%
“…A recent concept that may be relevant for many of these systems is the observation of nanoscale inhomogeneities that are thought to be intrinsic. These can take the form of nanoscale checkerboard- [2,3] or stripe-patterns [4], or less ordered structures [5,6,7,8] that are related to electronic phase separation. Phase separation is also found theoretically in computational models, which have been used to explain the large changes in conductivity with temperature and doping [9].…”
mentioning
confidence: 99%